전이성 위암의 항암치료 - 김성은; Sung Eun Kim; 박무인; Moo In Park; 이명훈; Myung Hun Lee (The Korean journal of gastroenterology, 2025)
Gastric cancer is the fourth most common malignancy in Korea and remains the fifth and seventh leading cause of cancer death in males and females, respectively. Although the survival rates for gastric cancer have improved, unresectable or metastatic gastric cancer still has an abysmal prognosis, and the five-year survival rate for patients with stage IV gastric cancer is approximately 6.6% in Korea. The treatment of patients with unresectable or metastatic gastric cancer is based on chemotherapy. A combination of fluoropyrimidine and platinum is the most widely used first-line treatment for gastric cancer worldwide. In recent decades, a better understanding of cancer biology has led to targeted therapies becoming the treatment paradigm for many cancers, including gastric cancer. In addition, immunotherapies have also been reported to improve survival in several cancers, particularly in patients with unresectable or metastatic gastric cancer who have failed multiple lines of chemotherapy. This review evaluates landmark studies on chemotherapy for unresectable or metastatic gastric cancer, including targeted therapies and immunotherapies. (Korean J Gastroenterol 2025;85:1-10)